Principles of Researching Health Disparities in Longitudinal Cohort Studies Enrolling Children - Hill, Carl V.; Hirschfeld, Steven; Stinson, Nathaniel S. (Frontiers in Pediatrics, 2021)
Heal th disparities are defined on the basis of specific demographic populations that, when compared to the general population, have a significant disparity on the rate of disease incidence, prevalence, morbidity, mortality, or survival. People that experience health disparities can be defined on the basis of race, ethnicity, geography, socioeconomic status, and other criteria. As the diversity of the United States broadens and increases, research on the origins and causes of health disparities becomes more important to support a healthy general population. Children are particularly sensitive to and vulnerable to health disparities due to the potentially life long consequences of events during periods of critical organ and intellectual development. The concept of health justice whereby each individual has the opportunity to realize their full health potential can only be realized with proper understanding and relevant data to frame policy and actions. The National Children’s Study was designed to incorporate the principles of the Federal Collaboration on Health Disparities Research in consultation with subject matter experts, community representatives, and ongoing evaluation to ensure high quality and relevant data on factors that impact health outcomes. This approach is applicable to other longitudinal cohort studies, and if adopted, has the potential to minimize health disparities and enhance health justice.